Introducing the World Health Organization Postpartum Family Planning Compendium. Issue 1 (3rd November 2016) - Sonalkar, Sarita; Gaffield, Mary E.
Abstract: The postpartum period offers multiple opportunities for healthcare providers to assist with family planning decision making. However, there are also many changing factors during the first year after delivery that can affect family planning choices. Given that several different documents have addressed WHO guidance on postpartum family planning, the electronic WHO Postpartum Family Planning Compendium (http://srhr.org/postpartumfp ) has been introduced. This resource integrates essential guidance on postpartum family planning for clinicians, program managers, and policy makers. The development of the Compendium included consultations with family planning experts, key international stakeholders, and web developers. Once the website had been created, user testing by family planning experts allowed for improvements to be made before the official launch. Future directions are adaptation of the website into a mobile application that can be more easily integrated to low‐resource settings, and translation of the content into French and Spanish. Abstract : The WHO Postpartum Family Planning Compendium is an electronic tool that integrates WHO guidance on postpartum family planning.